Design and Demonstration of a Smart Charging System for Plug-in Electric Vehicles - Sastry, Kartik V.; Holla, Shashank; Tater, Shreyas; Gustafson, Eric; Taylor, David G.; Leamy, Michael J. (IEEE Transportation Electrification Conference and Expo (Online), 2023)
This paper describes the development and demon-stration of a smart charging system for a plug-in electric vehicle (EV) that can help manage grid impacts. Our vehicle-external smart charging system supports charging Levels 1 and 2 defined in the SAE J1772 standard, and interfaces with the EV through (i) a standard charging cable, and (ii) a third-party telematics API (compatible with a wide range of EV manufacturers). The smart charging system interacts with the EV owner via a smartphone application to obtain charging requirements and preferences. User preferences inform an optimization objective function which captures multiple interests of the EV owner via a user-weighted sum of three performance metrics: cost of electricity, usage of renewable energy, and time-to-charge. An optimization-based feedback control algorithm determines an optimal set of time intervals, during which to charge the EV at a pre-defined, constant power level. Power flow to the EV is subsequently (dis)allowed accordingly by controlling a relay placed between the EV and the mains connection. Experimental results demonstrate minimum-cost charging of a 2021 Volvo XC90 Recharge using our prototype smart charging system.